2020
DOI: 10.3389/fnint.2020.00025
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Insular Functional Connectivity Changes Related to Mood and Fatigue Improvements in Major Depressive Disorder Following Tai Chi Training: A Pilot Study

Abstract: Objective: Tai chi (TC), a contemplative practice combining slow movements and deep breathing, has been shown to be clinically effective in alleviating depressive symptoms. Feelings of fatigue or low vitality often accompany major depressive disorder (MDD) though they are commonly overlooked and not well understood neurologically. By using resting state functional connectivity (rs-FC) using the insula as the seed, this study examines the relationship between mood and vitality symptoms in MDD and how they are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 74 publications
2
15
0
Order By: Relevance
“…But to my knowledge, although currently underway, little clinical research has been completed and published on brain imaging with mindful-movement practices and interoceptive bodily awareness. An exception is a recent study on tai chi and depression (Xu et al, 2020). Although bodily awareness was not assessed directly, the authors found connectivity changes indicating "a shift towards processing experience according to sensory rather than cognitive aspects .…”
Section: Resultsmentioning
confidence: 94%
“…But to my knowledge, although currently underway, little clinical research has been completed and published on brain imaging with mindful-movement practices and interoceptive bodily awareness. An exception is a recent study on tai chi and depression (Xu et al, 2020). Although bodily awareness was not assessed directly, the authors found connectivity changes indicating "a shift towards processing experience according to sensory rather than cognitive aspects .…”
Section: Resultsmentioning
confidence: 94%
“…There were 13 randomized control trials with 17 articles [16][17][18]20,24,25,27,28,32,33,[40][41][42][43][44][45][46], 8 cross-sectional studies with 12 articles [21][22][23]26,[29][30][31]34,[36][37][38][39], and 3 single group pre-and postcomparisons with 3 articles [15,19,35]. Among these 24 studies, 17 of them with 21 articles had elderly subjects who were 60 years and older [20][21][22][23][24]26,[29][30][31][33][34][35][36][40][41][42][43][44][...…”
Section: Resultsmentioning
confidence: 99%
“…Among these 24 studies, 17 of them with 21 articles had elderly subjects who were 60 years and older [20][21][22][23][24]26,[29][30][31][33][34][35][36][40][41][42][43][44][45][46], 4/24 studies with 8 articles had mixed age groups with subjects 21-70 years old [17,19,27,28,32,[37][38][39], and 3 studies had healthy young subjects [16,18,25]. The majority of these studies used healthy subjects [15,16,18,[20][21][22][23][24][25][26][27][28][29][30][31][33][34][35][36]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on prior evidence of beneficial effects of body awareness training on mental health conditions,[43,44] we did a Kruskal-Wallis ANOVA test, to examine the impact on average person measures on four specific groups: healthy adults with and without currently performing body awareness training; and adults with mental health conditions with and without currently performing body awareness training. The result showed that adults with mental health conditions who are not doing any body awareness training have a significantly higher average person measure location (Median (IQR)=0.83(0.89) logits, p <0.0001)) compared to the other three groups (Fig 4).…”
Section: Resultsmentioning
confidence: 99%